Uma proposta de estudo de integral dupla com o auxílio do software Geogebra - ALCANTARA, Yuri Castro (2019)
This work makes a study on the double integrals, using as support Geogebra software to build the flat and spatial figures that appear during the course of the study. The importance of software in these constructions is emphasized, since they are difficult to construct by the free hand by the student and the teacher in their classes. It should also be emphasized that the visualization of these figures by the students can facilitate the understanding of the theory of double integrals, reducing the abstract content of mathematics teaching, contributing significantly to students' learning. In addition, a tutorial of the constructions developed is presented, so that it supports other students who wish to study with the help of Geogebra software.